A Conversation Diary: A Teaching and Learning Speaking Media - Neti Rosiana Fadilah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2020)
This research aims to analyze the use of conversation diary as a teaching and learning speaking media at ASMI Citra Nusantara Banjarmasin. This research is done in Classroom Action Research (CAR) within 3 cycles. Each of the cycle is started by assessing classroom problems, and continues with planning, acting, observing, and reflecting. Each cycle has 5 hours with 17 student as participant. In the first cycle, there’s less than 50% student passing at passing grade, according to many students who are weak in mastering grammar and vocabulary and not confident in speaking. But the result more better in the next cycle, because students began to enjoy the activities of convertible diary even though there were still passive students. In conclusion, this study proved that Conversation Diary could improve the students’ speaking skill better and help decreasing the students’ anxiety. With enough length of time, it would gain better result.